Pengaruh Risiko Likuiditas dan Ukuran Perusahaan Terhadap Profitabilitas Perbankan di Bursa Efek Indonesia - Dewi, Nurma Gupita (IAIN Surakarta, 2020)
This study aims to analyze the effect of liquidity risk and firm size on profitability in the banking sector listed on the Indonesia Stock Exchange in the period 2016-2018. Liquidity risk in this study is proxied by using factors that can be managed by the bank to avoid the threat of liquidity risk.Liquidity risk in this study is proxied by loan debt ratio, while firm size uses a natural logarithm from total assets. The sampling technique uses a purposive sampling method that is by using certain criteria. The population in this study was all banking companies listed in Indonesia Stock Exchange. The sample used in this study are 30 banks.The analysis was carried out using multiple regression analysis. The results of this study indicate that loan debt ratio has aninsignificant effect on bank profitability. Firm size has a positive Â and significant effect toward profitability in banking sector in Indonesia.Keywords: Liquidity Risk, Firm Size and ProfitabilityJEL Classification Codes:Â C12, G21, L25